Sustainability of Packaged UHT Cow’s Milk Products Using the Multidimensional Scaling (MDS) Method - Astati, Astati; Hifizah, Amriana; Qurniawan, Anas (Faculty of Animal Science, Universitas Gadjah Mada, 2025)
Product positioning is how a product is defined by consumers in terms of the attributes of competitors or the place where the product is distinguished in the minds of consumers compared to other products. This study aims to analyze the sustainability of packaged UHT cow's milk products in the market using the Multidimensional Scaling (MDS) non-metrik method. This research was conducted in Makassar City, South Sulawesi, specifically at shopping centers frequently visited by consumers, namely Lotte Mart and Satu Sama, from May to July 2024. The sampling technique used was accidental sampling, where anyone who happened to meet the researcher while purchasing UHT cow's milk and was deemed suitable as a data source was selected. The total number of respondents obtained during the study was 65. The analysis results show that Indomilk UHT and Frisian Flag UHT have superior positions in terms of storage temperature, packaging design, ease of use, and ease of storage, located in quadrant I. Meanwhile, Ultra Milk UHT and Diamond Milk UHT compete closely in terms of product innovation and discounts, located in quadrant III. These findings indicate that each brand has certain competitive advantages that can be leveraged for product development and more effective marketing strategies. To achieve product sustainability, the development of packaged UHT cow's milk products needs to focus on attributes valued by consumers, thus allowing for increased competitive advantage